2021
DOI: 10.3847/1538-4357/ac07a1
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Filament Formation Mechanisms in Magnetized Molecular Clouds

Abstract: Recent observations of molecular clouds show that dense filaments are the sites of present-day star formation. Thus, it is necessary to understand the filament formation process because these filaments provide the initial condition for star formation. Theoretical research suggests that shock waves in molecular clouds trigger filament formation. Since several different mechanisms have been proposed for filament formation, the formation mechanism of the observed star-forming filaments requires clarification. In … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 63 publications
1
30
0
Order By: Relevance
“…Moreover, studies of Doi et al (2021) and Bialy et al (2021) have suggested that bubbles in the Perseus-Taurus region have formed the Perseus molecular cloud. Formation of clouds through expanding bubbles can result in an arc-shaped magnetic field morphology associated with the filamentary structures (Inoue & Fukui 2013;Inutsuka et al 2015;Inoue et al 2018;Abe et al 2021). These cloud-formation studies suggest that dense filamentary molecular clouds form via interaction of a shock front and a pre-existing inhomogeneous dense cloud, where the magnetic fields are predicted to bend and allow for further mass accumulation, creating even denser filaments.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies of Doi et al (2021) and Bialy et al (2021) have suggested that bubbles in the Perseus-Taurus region have formed the Perseus molecular cloud. Formation of clouds through expanding bubbles can result in an arc-shaped magnetic field morphology associated with the filamentary structures (Inoue & Fukui 2013;Inutsuka et al 2015;Inoue et al 2018;Abe et al 2021). These cloud-formation studies suggest that dense filamentary molecular clouds form via interaction of a shock front and a pre-existing inhomogeneous dense cloud, where the magnetic fields are predicted to bend and allow for further mass accumulation, creating even denser filaments.…”
Section: Introductionmentioning
confidence: 99%
“…This velocity structure has also been observed toward another filament, the Musca filament (Bonne et al 2020). More recently, in a theoretical study, Abe et al (2021) proposed a classification of filament formation mechanisms resulting from the variation in the relative importance between the shock velocity, the turbulence, and the magnetic field strength (see also the theoretical study by Chen et al 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulations by Maeda et al (2021) demonstrated ∼10 4 M e massive clump formation driven by a large-scale H I gas flow that mimics galactic interactions. Abe et al (2021) showed that fast (>10 km s −1 ) gas flow is more favorable for massive filament formation with a line mass of >100 M e pc −1 . From observational perspectives, recent ALMA studies in M33 also found massive filaments with high-mass cluster formation associated with galaxy-galaxy interactions and other galaxyscale gas motions related to a spiral arm (Tokuda et al 2020;…”
Section: Colliding Flows Promoting the Protocluster Formation In N159...mentioning
confidence: 99%